Analysis of the Educational Conditions of Two-Year-Old Children in Kindergartens in Slovakia: A Study from Teachers' Perspectives - Lipnická, Milena (Open Access Indonesia Journal of Social Sciences, 2024)
The aim of the research was to find out teachers' opinions on selected conditions of upbringing and education of 2-year-old children in kindergartens in Slovakia. These may influence decisions about the admission of 2-year-old children to kindergarten and the quality of the conditions of their education. The research method was an online questionnaire, created and processed in SURVIO software. The survey was conducted in spring 2023. 594 kindergarten teachers completed the questionnaire. The results of the research showed that the family and the nursery are preferred for the upbringing and education of 2-year-old children (50.5%). If 2-year-old children are admitted to kindergarten, they must have certain prerequisites and be in a class with their peers (57.1%). They cannot wear diapers in kindergarten (79.7%) and have to cope with separation from parents (78.2%). 2-year-olds can be in kindergarten if a teacher's assistant works in the classroom (61.5%). Teachers (55.4%) do not prefer a health worker or caregiver with 2-year-olds (51%). For pedagogical work with 2-year-old children, teachers only need a secondary education (39.2%), some already have a bachelor's degree (27.2%). The results confirmed the insufficient methodological support of the issue by the state (60.5%) and the importance of the development of information and methodological material in the KEGA project No. 001UMB-4/2022. It will be used by teachers to improve the conditions for the education of two-year-old children in kindergartens in Slovakia.